2023
DOI: 10.1093/jxb/erad326
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate starvation: response mechanisms and solutions

Imani Madison,
Lydia Gillan,
Jasmine Peace
et al.

Abstract: Phosphorus is essential to plant growth and agricultural crop yields, yet the challenges associated with phosphorus fertilization in agriculture, such as aquatic runoff pollution and poor phosphorus bioavailability, are increasingly difficult to manage. Comprehensively understanding the dynamics of phosphorus uptake and signaling mechanisms will inform the development of strategies to address these issues. This review describes regulatory mechanisms used by specific tissues in the root apical meristem to sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…We found that under LPi conditions, the treatment with 50 mM Phi severely reduced shoot and root growth (Figure 1). In Pi-deprived seedlings, 50 mM Phi also attenuated the formation of lateral roots and the accumulation of anthocyanins, which are characteristic components of the PSR in Arabidopsis [29,30]. Phi negatively impacted metrics associated with the root architecture, such as lateral root number, primary root length, root weight, total root length, and convex hull (Figure 1ej).…”
Section: Phi Suppresses Pi Starvation Responses and Positively Affect...mentioning
confidence: 96%
“…We found that under LPi conditions, the treatment with 50 mM Phi severely reduced shoot and root growth (Figure 1). In Pi-deprived seedlings, 50 mM Phi also attenuated the formation of lateral roots and the accumulation of anthocyanins, which are characteristic components of the PSR in Arabidopsis [29,30]. Phi negatively impacted metrics associated with the root architecture, such as lateral root number, primary root length, root weight, total root length, and convex hull (Figure 1ej).…”
Section: Phi Suppresses Pi Starvation Responses and Positively Affect...mentioning
confidence: 96%
“…P is a major macronutrient that strongly influences plant growth and productivity, including in rice ( Oryza sativa ), a major crop worldwide [ 3 , 4 ]. Phosphorus stress negatively regulates metabolic processes [ 5 , 6 , 7 ], and plants have evolved various adaptive strategies that enable them to withstand this stress. To cope with limited phosphate availability, plants have developed a phosphate homeostasis mechanism that mobilizes and stores Pi from soil, which is utilized under stress [ 4 ].…”
Section: Introductionmentioning
confidence: 99%